Inhibition of PI3K/AKT/mTOR Signalling Pathway Activates Autophagy and Suppresses Peritoneal Fibrosis in the Process of Peritoneal Dialysis - Jia, Miao; Qiu, Hong; Lin, Lihua; Zhang, Shun; Li, Damei; Jin, Donghua (Frontiers in Physiology, 2022)
Peritoneal dialysis (PD) is an important part of replacement therapy for kidney failure. However, long-term PD treatment can cause peritoneal fibrosis. Autophagy may be involved in the pathological mechanism of peritoneal fibrosis (PF). Although autophagy is currently known to be involved in course of PF, its specific effects still lack in-depth research. In this experiment, a high-glucose (HG)-induced peritoneal fibrosis rat model was successfully established via intraperitoneal injection of HG peritoneal dialysate, and the phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002 and the mechanistic target of rapamycin (mTOR) inhibitor rapamycin were used to treat peritoneal fibrosis rats. In addition, in vitro studies of high glucose-induced peritoneal fibrosis were performed using rat peritoneal mesothelial cells (PMCs). In vivo and in vitro experiments showed that LY294002 and rapamycin effectively inhibited the process of PF induced by high glucose. In addition, LY294002 and rapamycin were found to alleviate fibrosis b y eliminating intracellular reactive oxygen species (ROS) levels, promoting the expression of the epithelial mesenchymal transdifferentiation proteins zonula occludens-1 (ZO-1) and E-cadherin, and inhibiting the expression of p-PI3K, PI3K, p-mTOR, mTOR, the fibroblast-specific proteins ferroptosis suppressor protein 1 (FSP1) and alpha-smooth muscle actin (α-SMA). Moreover, LY294002 and rapamycin promoted expression of autophagy-related proteins LC3-II/I, p62, and beclin-1. The current data indicated that inhibition of PI3K/Akt/mTOR signaling pathway activated autophagy and suppressed PF in the process of PD. Therefore, intervention in this signalling pathway may become a research goal for the prevention and treatment of PF, which has important clinical significance.